Democratizing Global Justice: The World Tribunal on Iraq - Gerson, Janet (In Factis Pax: Journal of Peace Education and Social Justice, 2013)
Can justice be enlarged to the global level? This article explores the World Tribunal on Iraq (WTI), a global civil society tribunal, and its contributions to democratizing post-conflict justice deliberations. This study reflects the WTI’s self-understanding as enacting an innovative reclaimative justice tribunal form.